2010
DOI: 10.1139/x10-095
|View full text |Cite
|
Sign up to set email alerts
|

Determining the main and interactive effect of age and clone on wood density, microfibril angle, and modulus of elasticity for Pinus radiata

Abstract: Detailed radial measurements of wood properties, taken at breast height, were obtained from control pollinated seedlings and a selection of 13 year old radiata pine ( Pinus radiata D. Don) clones. Using these data the key objectives of this study were to determine (i) the magnitude of mean clonal variation in modulus of elasticity (MOE) and properties affecting MOE (density and microfibril angle (MFA)) and (ii) whether there is a significant age × clone interaction for these traits. All wood properties were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…This increase in the proportional size of the juvenile wood core is probably more significant for log utilisation than the quantitative changes to individual wood properties (Cown 1992). The overall strong trend between stress-wave velocity (assumed to be only estimating the stiffness of the outerwood) and stand density implies a solid relationship between the latter and timber stiffness, in line with results from other studies (Lasserre et al 2005;Watt et al 2010). The current results, however, do not support the findings from another study in New Zealand (Grabianowski et al 2004) or the results from a mature spacing study in Chile (Soto et al 2012) which concluded that initial stand density (2500, 1667, 833 and 625 stems ha −1 across four sites) did not influence stress-wave velocity.…”
Section: Discussionsupporting
confidence: 88%
“…This increase in the proportional size of the juvenile wood core is probably more significant for log utilisation than the quantitative changes to individual wood properties (Cown 1992). The overall strong trend between stress-wave velocity (assumed to be only estimating the stiffness of the outerwood) and stand density implies a solid relationship between the latter and timber stiffness, in line with results from other studies (Lasserre et al 2005;Watt et al 2010). The current results, however, do not support the findings from another study in New Zealand (Grabianowski et al 2004) or the results from a mature spacing study in Chile (Soto et al 2012) which concluded that initial stand density (2500, 1667, 833 and 625 stems ha −1 across four sites) did not influence stress-wave velocity.…”
Section: Discussionsupporting
confidence: 88%
“…This approach involves sampling a small number of large trees that are difficult and slow to handle, so it tends to be for research purposes rather than for operational purposes. For example, in a recent study, Watt et al (2010) analyzed a 13-year-old clonal trial taking two ramets of 13 clones. These authors suggested that modulus of elasticity (MoE) assessments from age 5 onwards could be used to identify clones with high MoE.…”
Section: Application Optionsmentioning
confidence: 99%
“…Some of these properties (e.g., high microfibril angle) are the least desirable and most variable in corewood-arbitrarily defined as the ten growth rings next to the pith-inducing negative effects on mechanical properties and dimensional stability. Traditionally, corewood properties have been either targeted through the improvement of basic density (Harris et al 1976) or neglected (Walker and Nakada 1999) on the grounds that wood quality will gradually improve from pith to bark, eventually achieving acceptable wood quality in the outerwood (Watt et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…He also suggested that it was worth developing an early selection for tree quality [6]. Moreover, Watt et al (2010) suggested that P. radiata clones with high average stiffness can be selected from trees aged 5 years [7]. Emms et al stated that the early screening of tree quality has benefits to the forestry industry, potentially yielding better wood quality [1,8].Acoustic techniques such as longitudinal stress waves, acoustic resonance, and ultrasound have been used to determine the mechanical properties of wood materials for many years [9,10].…”
mentioning
confidence: 99%